RANCANG BANGUN APLIKASI RETENSI REKAM MEDIS BERBASIS CLOUD COMPUTING DI RUMAH SAKIT SURABAYA: Aplikasi Retensi Rekam Medis - Mochammad Arifin Arifin (Yayasan Pendidikan Medika Indonesia, 2022)
DKT Surabaya Hospital, initially as a place for military care (TPT) and then developed into a place for family care (TPK). In terms of improving the quality of service to the community and the start of the 4.0 era, it is time for hospitals to use applications for managing Medical Record files that are connected to the server. So far, the Retention System is done manually and the books are stored somewhere in physical form, and when a search is carried out one has to open the files to be searched on a stack, this causes time inefficient. The solution of this research aims to provide a Medical Record retention system application at DKT Surabaya Hospital. This research data is stored using SQL Server. In the process of working on this research, the writer carried out the data analysis phase using the System Development Live Cycle (SDLC) method and the Waterfall model in development. The result of the research is the formation of a medical record retention system application consisting of 4 tables in the database. The output of this Retention application is to store and display patient Medical Record Retention data. The result of this research is the formation of a retention system that has been created and has been tested using blackbox testing with the results of forms, tables in the database, and reports in accordance with the provisions.